Hak Prerogatif Presiden dalam Perspektif Hukum Tata Negara Indonesia - Ni'matul Huda (Jurnal Hukum IUS QUIA IUSTUM, 2001)
The prerogatives of the presiden to four country have been limitated significantly since the General Assembly (MPR) has amended the consfitutiom Many its articles which had empowered the president to rule the state authoritatively have been corrected by the amendment as the president shouldget approvalfrom parliament(DPR) is some certain cases orconsideration from the Representative Body ofSupreme Court in the otherones.In order to control President's power the parliamentwould be obligedto exploit its rights extensively and proportionally. However, it would be veryimportant to declare his power on the constitution or codes with clean